Multicriteria evaluation of Lithuanian banks from the perspective of their reliability for clients - Ginevičius, Romualdas; Podvezko, Valentinas (Journal of Business Economics and Management, 2008)
In recent years, efforts have been made to rank banks according to their reliability. However, the methods used for this purpose are not accurate. The analysis shows that reliability of banks is a complex phenomenon which can only be described by a set of criteria. The task is complicated by the fact that the criteria used have various dimensions as well as being oppositely directed. To solve the above problems, multicriteria evaluation methods, allowing the values of all the criteria of different dimensions and changeability to be integrated into a single generalized quantity, may be used. First published online: 14 Oct 2010